Gender and social justice in Wales - Charles, Nickie; Davies, Charlotte Aull (Gender studies in Wales., 2010)
The authors assess how policies developed by the National Assembly for Wales are affecting gender inequalities and investigates whether they are having an impact on social justice for women in Wales.